Efficacy and safety of oral sulfate tablet vs. polyethylene glycol and ascorbate for bowel preparation in children - Choi, Sujin; Kim, Ji Sook; Choe, Byung-Ho; Kang, Ben (Frontiers in Pediatrics, 2024)
Background and Aim: Bowel preparation for pediatric colonoscopy presents several challenges. However, no bowel preparation regimen is universally preferred for children. We aimed to investigate the efficacy and safety of oral sulfate tablet (OST) in pediatric bowel preparation.Methods: This study retrospectively analyzed data from children who received 2L of polyethylene glycol and ascorbate (PEG/Asc) or OST for bowel preparation between 2021 and 2023. A comparative analysis was conducted between the two groups.Results: A total of 146 patients were included (2L PEG/Asc: 115, 73.0% vs. OST: 31). No significant difference was observed in the total BBPS score (median 8.0 vs. 8.0, P=0.152) and the total OBPS score (median 5.0 vs. 3.0, P = 0.152) between the two groups. No significant difference was noted in the ratio of a bubble score of 0 (73.0% vs. 93.5%, P = 0.132). The incidence of abdominal pain was significantly lower in the OST group (32.2% vs. 3.2%, P = 0.002). The VAS score for overall satisfaction was significantly higher in the OST group (4.0 vs. 7.0, P < 0.001). For the next colonoscopy bowel preparation, a higher proportion of patients in the OST group showed a willingness to use the same preparation regimen (33.9% vs. 83.9, P < 0.001).OST was as efficacious and safe as 2 L of PEG/Asc for pediatric bowel preparation. The satisfaction level was higher with OST than with 2 L of PEG/Asc. OST may be considered a good alternative for children with poor compliance during bowel preparation.